2022
DOI: 10.1093/rb/rbac030
|View full text |Cite
|
Sign up to set email alerts
|

Crosslinking and functionalization of acellular patches via the self-assembly of copper@tea polyphenol nanoparticles

Abstract: Decellularization is a promising technique to produce natural scaffolds for tissue engineering applications. However, non-crosslinked natural scaffolds disfavor application in cardiovascular surgery due to poor biomechanics and rapid degradation. Herein, we proposed a green strategy to crosslink and functionalize acellular scaffolds via the self-assembly of copper@tea polyphenol nanoparticles (Cu@TP NPs), and the resultant nanocomposite acellular scaffolds were named as Cu@TP-dBPs. The crosslinking degree, bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…These functional patches possessed antibacterial and proangiogenic activities. 112 Antibody immobilization on the surface of nanoparticles to prevent recognition by antigen is an important area of research in nano-biotherapeutics. 113 Electrostatic and hydrophobic interactions are responsible for antibody binding on nanoparticles; these binding forces are usually difficult to control.…”
Section: Networkmentioning
confidence: 99%
See 2 more Smart Citations
“…These functional patches possessed antibacterial and proangiogenic activities. 112 Antibody immobilization on the surface of nanoparticles to prevent recognition by antigen is an important area of research in nano-biotherapeutics. 113 Electrostatic and hydrophobic interactions are responsible for antibody binding on nanoparticles; these binding forces are usually difficult to control.…”
Section: Networkmentioning
confidence: 99%
“…Cardiac patch graft models confirmed that Cu@TP-dBP patches demonstrated improved in-growth of functional blood vessels and extracellular matrix remodeling within 60 days. These functional patches possessed antibacterial and proangiogenic activities …”
Section: Self-assembly Of Metal–phenolic Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al . [ 178 ] functionalized bovine pericardia dECM scaffold with copper@tea polyphenol self-assembly nanoparticles based on the coordination of tea polyphenol with copper ions. As expected, the scaffold maintained the antimicrobial activity of nanoparticles, which also exhibited anti-calcification, remodeling and integration properties for cardiovascular applications.…”
Section: Decm–bioactive Factor Composite Materialsmentioning
confidence: 99%
“…From nanoparticles and hydrogels to various types of scaffolds and patches [ 118 ], the application of innovative biomaterials in the field of therapeutic factor delivery has shed new light on the CVD therapy [ 119 , 120 ]. In order to transfer metal ions that may have therapeutic effects to the diseased regions, researchers have been introduced a variety of carriers [ 121 ].…”
Section: Engineering Strategies For Metallic Ion Delivery For Cardiov...mentioning
confidence: 99%